I Love to Cuddle illustrated by Claude K. Dubois. - Norac, Carl.; Dubois, Claude K. (New York : Scholastic Inc., 1998)
Lola is lonely when Mommy and Daddy go out for a while so she creates her very own Cuddle Island. Mommy and Daddy are in for a surprise.
Accelerated Reader AR